Revitalisasi Keadilan dalam Kasus Pungutan Liar Bantuan Sosial PKH terhadap Korban dari Perspektif Viktimologi - Rifalina Fredita; Gracia Violeta; Dinda Kartika Dewi; St Nada Oktaviani; Fidela Humaira Ismoyo C; Isni Fitria Ramadhani (Jurnal Hukum, Administrasi Publik dan Negara, 2025)
Extortion in the distribution of social assistance for the Family Hope Program (PKH) is one of the structural problems that hinders the effectiveness of the program in empowering the poor. This practice not only harms the recipients of assistance, but also violates the principles of social justice. This article aims to examine the case of extortion in PKH from a victimology perspective, focusing on its impact on victims, both psychologically and socio-economically. This study uses an empirical legal methodology using a field research approach and a sociological legal approach. The data obtained was processed qualitatively which was then analyzed descriptively. The results of the study show that victims of extortion experience greater losses, not only in the form of loss of funds, but also in the form of damage to trust in social and state institutions. In addition, this study proposes several steps to revitalize justice in handling extortion cases, including increasing supervision, public education, and bureaucratic reform that can restore public trust in the PKH program. Thus, revitalizing justice in this context is expected to create a more just social environment and reduce the practice of extortion in the future.